Visualizing the Rise of Authoritarian Carbon (1992–2022) - John Chung-En Liu (Socius)
Using data from V-Dem, Freedom House, and the Global Carbon Budget, the author visualizes how authoritarian and nondemocratic regimes have sharply increased their share of global CO 2 emissions over the past three decades. Authoritarian regimes now account for more than 60 percent of emissions, while liberal democracies contribute roughly one-third. This shift has significant implications for climate governance. Yet climate change remains peripheral in sociology, in which research continues to focus on Western democracies. Sociology can play a critical role in examining how authoritarian environmental governance shapes both environmental outcomes and climate justice.